Punjab Medicolegal Manual General Guidelines for Medical Practioners - DS Bhullar; Preetinder Singh Chahal (GMC Patiala Journal of Research and Medical Education, 2021)
Govt. of Punjab Medicolegal Manual was drafted by certain amendments in the guidelines for conduct and examination of medicolegal cases in the State of Punjab keeping in view the multiple difficulties being faced in medicolegal and post-mortem working. The manual is a combine of the original Punjab Medical Manual with inputs incorporated from the relevant latest other Indian state, national and international guidelines relating to the medicolegal examination of living and dead persons along with the practical experience of forensic medicine and other experts.